The energy absorption of damaged braided and non-crimp fibre composite material structures - Bottome, Kristofer John (2006)
The effects of pre-existing damage on the mode of failure and energy absorption characteristics of Non-Crimp Fabric (NCF) and biaxially braided tubular sections under axial loading were considered. Loading rate effects were incorporated by testing at quasi-static rates and impact rates up to 7ms-1 and the pre-existing damage was simulated through stress concentrations and out-of-plane impact damage. Circular and square geometries were tested, and a range of NCF and braided fibre architectures were investigated.